Antitumor effect of mifepristone on human endometrial stromal cell line - Luković, Jovan; Milosavljević, Zoran; Zečević Luković, Tanja; Mitrović, Marina; Andjelković, Marija; Zelen, Ivanka; Stanojević Pirković, Marijana; Nikolić, Ivana (Vojnosanitetski pregled, 2021)
Background/Aim. The main cause for development of endometrial hyperplasia is unopposed effect of estrogen on endometrial cells. The aim of our study was to investigate and compare cytotoxic and apoptotic effects of mifepristone on human endometrial stromal cell line for the first time. Both percentage of cytotoxic and apoptotic cells were determined after 24 h treatment with different doses of mifepristone. Methods. The percentage of cytotoxic cell was evaluated by viability assay while the percentage of apoptotic cells was determined using flow cytometry. Determination of apoptotic effects was confirmed using immunofluorescence method determining expression and localization of active Bax and Bcl-2 proteins. Results. Our results indicated that mifepristone induced cytotoxic and apoptotic effect on human endometrial stromal cell line (ThESC) through changes in expression level of Bcl-2 and active Bax proteins. Conclusion. Cytotoxic and pro-apoptotic effects of mifepristone on human endometrial stromal cell line in vitro was investigated in this study for the first time. It is crucial to point out that mifepristone expressed both cytotoxic and pro-apoptotic effect on ThESC cell line. Our results may contribute to determination of localization and expression level of the crucial proteins involved in apoptosis in ThESC cell line after the treatment with the lowest cytotoxic doses of mifepristone.
Keywords: endometrial hyperplasia; mifepristone; apoptosis; cell death; carcinoma.